A Quasi-Experimental Evaluation of a School-Based Prescription Opioid Misuse Education Program. (September 2021) - Carson, Dena C.; Lane, Emelyne B.
The use of prescription opioids is a matter of concern among academics and practitioners, but there remains a lack of programming to target this issue. One program, This Is (Not) About Drugs (TINAD), is intended to address part of this need by altering youth perceptions of the risks associated prescription opioid misuse as well as heroin. This study presents results from a quasi-experimental evaluation of TINAD. Propensity score matching techniques were used to account for selection effects across treatment and comparison groups. Program participants demonstrated increases in understanding of the similarities between prescription opioids and heroin and the risks associated with prescription opioid misuse. While these results are promising, TINAD requires a more rigorous evaluation of its effectiveness.